Day 2 Wed, October 23, 2019 2019
DOI: 10.2118/196767-ms
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Assisted Steam Flooding Technology after Steam Flooding - A Case Study in Block J6 of Xinjiang Oilfield

Abstract: Currently Block J6 is in the later stage of steam flooding after 27 years’ steam injection, its recovery factor is about 50%, and the water cut is more than 95%. Particularly, the present steam oil ratio is about 12 m3(CWE)/t which has reached the economic limit and is in ineffective development. Cores from four post steam flooding drilling wells show that only top 2-3m of the total 25-30m pay zone has a steam chamber which is the main steam channel and its residual oil saturation is about 20%, the other 22-27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This phenomenon did not occur in the steam-only-treated wells. Both the lab and field tests showed that this type of emulsified foam oil could significantly reduce the viscosity of heavy oil [16,17]. Further research is required to reveal what mechanisms lead to the formation of this type of emulsified foam oil, which is created when steam and CO 2 are coinjected to recover heavy oil.…”
Section: Classification Of Production Wells In the Test Areamentioning
confidence: 99%
“…This phenomenon did not occur in the steam-only-treated wells. Both the lab and field tests showed that this type of emulsified foam oil could significantly reduce the viscosity of heavy oil [16,17]. Further research is required to reveal what mechanisms lead to the formation of this type of emulsified foam oil, which is created when steam and CO 2 are coinjected to recover heavy oil.…”
Section: Classification Of Production Wells In the Test Areamentioning
confidence: 99%